2020
DOI: 10.3389/fpsyg.2020.558190
|View full text |Cite
|
Sign up to set email alerts
|

Unmet Supportive Care Needs Among Women With Breast and Gynecological Cancer: Relevance of Attachment Anxiety and Psychological Distress

Abstract: Objective: Attachment anxiety and avoidance are known risk factors for the development of unmet needs and poor well-being among patients with chronic diseases. Few studies have addressed this in individuals with cancer. We aimed to explore the relationship between supportive care needs, attachment styles and distress in women with breast and gynecological cancer. Methods: Using a cross-sectional paper-pencil (n = 157) and online survey (n = 614), a total of 771 patients with breast or gynecological cancer comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 59 publications
(86 reference statements)
1
7
0
6
Order By: Relevance
“…Our findings suggest that people who suffered trauma in childhood also have more difficulty adhering to medical recommendations. Several studies have shown that people with childhood trauma are more likely to develop insecure attachment styles, which are associated with difficulties in seeking help and maintaining stable relationships ( Pearlman and Courtois, 2005 ; Clark et al, 2011 ; Millar et al, 2021 ) and other factors related to somatic medicine ( Graetz et al, 2013 ; Graf et al, 2020 ; Graetz et al, 2021 ). Therapeutic alliance, a marker of a stable relationship, indeed appears to play an important role in adherence ( Pringle and Fawcett, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings suggest that people who suffered trauma in childhood also have more difficulty adhering to medical recommendations. Several studies have shown that people with childhood trauma are more likely to develop insecure attachment styles, which are associated with difficulties in seeking help and maintaining stable relationships ( Pearlman and Courtois, 2005 ; Clark et al, 2011 ; Millar et al, 2021 ) and other factors related to somatic medicine ( Graetz et al, 2013 ; Graf et al, 2020 ; Graetz et al, 2021 ). Therapeutic alliance, a marker of a stable relationship, indeed appears to play an important role in adherence ( Pringle and Fawcett, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…La mayor parte de la investigación sobre artículos seleccionados de este estudio de revisión sistemática muestra que las necesidades insatisfechas más altas en sobrevivientes de cáncer ginecológico y de mama son las necesidades de información y las necesidades de apoyo psicológico (9,12,13,17,19,21,(23)(24)(25)(26)(27)(28) . Esta necesidad no solo se siente en las sobrevivientes de cáncer ginecológico y de mama en el período temprano del diagnóstico, sino que también se siente como una necesidad insatisfecha desde el inicio del diagnóstico cuando el período de tratamiento hasta las fases de rehabilitación, terminal y paliativa (9,17,26) .…”
Section: Necesidades Insatisfechas En Sobrevivientes De Cáncer Gineco...unclassified
“…Los efectos de las necesidades insatisfechas de información y apoyo psicológico son mayor angustia, tendencia a experimentar depresión y disminución de la calidad de vida (9,21,23,25) . Otros impactos incluyen una mayor morbilidad que sienten los sobrevivientes, caracterizada por un empeoramiento de los síntomas físicos y quejas de los efectos secundarios del tratamiento (21) .…”
Section: Necesidades Insatisfechas En Sobrevivientes De Cáncer Gineco...unclassified
“…Public health policies should take into account this situation and should plan interventions providing psychological support to patients in order to reduce emotional distress and, hence, years lived with a disability. This psychological support should be provided as soon as the disease has been diagnosed, since a cancer diagnosis produces emotional distress in patients and their families [ 1 , 2 , 3 , 4 , 5 ]. Depending on the study, the incidence of clinically significant distress could range between 24% [ 6 ], 52% [ 7 ] and 61% [ 8 ].…”
Section: Introductionmentioning
confidence: 99%